LATIHAN RELAKSASI PERNAPASAN (HIPNOSIS) PADA IBU HAMIL UNTUK PERSIAPAN PERSALINAN - Novy Ramini Harahap; Mila Syari; Novitri Adelina Sipayung; Evaria Manurung (Jurusan Kebidanan Poltekkes Kemenkes Riau, 2022)
Primigravida pregnant women almost all experience worry, anxiety, and fear both during pregnancy, during labor and after delivery. The release of these stress hormones causes systemic vasoconstriction, including constriction of the uterine vasa utero which causes disruption of blood flow in the uterus, so that oxygen delivery to the myometrium is disrupted and results in weak uterine muscle contractions. This incident causes the delivery process to take longer. The way to create a calm condition in the body so that it is comfortable and calm can be done through hypnosis. Hypnosis / Hypnobirthing can be used to deal with and undergo pregnancy and preparation for childbirth in a natural, calm, and comfortable way as well as the mental health of the fetus. Hypnobirthing has several benefits including reducing pain, increasing the incidence of spontaneous labor, reducing the risk of surgery, accelerating the recovery of postpartum mothers, helping oxygen supply to the baby during the delivery process. The purpose of this community service activity is to encourage behavior change and equip mothers to cope with breathing during the sick delivery process. The method used is the hypnosis/hypnobirth counseling method at the time of delivery which is given education to pregnant women in the third trimester. Keywords: Hypnosis, Pregnancy